AI Readiness, Perceptions, and Resilience Impact on Supply Chain Performance in Tangerang - Cia, Handi Jonathan (Gema Wiralodra, 2024)
This study aims to analyze the influence of AI Readiness, Perceived Usefulness, Perceived Ease of Use, Behavioral Intention, and Supply Chain Visibility on Supply Chain Performance, with Supply Chain Resilience as a mediating variable. The research was conducted among employees of companies involved in the supply chain in the Tangerang area. The study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The results show that AI Readiness, Perceived Ease of Use, and Supply Chain Visibility have a significant effect on Supply Chain Performance. In addition, Supply Chain Visibility also significantly influences Supply Chain Resilience, which in turn contributes to Supply Chain Performance. On the other hand, Perceived Usefulness and Behavioral Intention do not have a significant impact on Supply Chain Performance. These findings highlight the importance of technology readiness, supply chain visibility, and supply chain resilience in supporting operational performance and competitive advantage in the modern era. The study also provides strategic insights for companies to invest in artificial intelligence-based technologies and strengthen supply chain integration